Analisis Kualitas Pelayanan Publik Pada Kantor Kecamatan Pasirwangi Kota Garut - Resti, Resti; Mulawarman, Aditia; Diana, An-Nisa (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Improvement and public demand for effective, efficient and satisfying public services from government employees as public services are increasingly popular. This is related to the development of needs, desires and expectations of the community which continues to grow and is increasingly up-to-date. In Government Regulation No. 18 of 2018 concerning Sub-districts, the sub-district government is obliged to provide guidance to every member of the community in order to realize the tasks of regional autonomy as they should have been stipulated in the regulations and in implementing their duties and functions. Organizations really need public services in the fields of government, development, and society. This study aims to determine and analyze the quality of public services in the Pasirwangi district of Garut City. This study uses qualitative research methods in a way that describes synergistic problems when the research is carried out. Data collection techniques are carried out by observation, interviews and documents. The instruments used in this study were observation sheets, interview sheets, and structured documentation made by the researchers themselves. the level of timeliness and service strategy is quite good so that people are quite enthusiastic in using public services.